The Effect of Electronic Medical Record Implementation on The Performance of Medical Record Officers - Oktamifany, Noerwindi; Wahab , Syaikhul (MultiTech Publisher, 2024)
Electronic medical records allow health care providers to be able to serve efficiently and are more secure in terms of security in accessing and recording various patient medical information, in its implementation electronic medical records become more effective on the performance of medical record officers. This study aims to determine the effect of electronic medical record implementation on the performance of outpatient medical record officers at X Hospital, Bandung City. The research method used is quantitative method by distributing questionnaires to 15 respondents of outpatient medical record officers. The results in this study, the effect of the implementation of electronic medical records on the performance of outpatient medical record officers amounted to 55.1% with positive results. From this study, problems were found including: (1) The lack of human resources in mastering technological developments. (2) There is a double medical record number. (3) There is still a lack of facilities and infrastructure that can interfere with the performance of electronic medical record officers in outpatient services.